2010
DOI: 10.1021/jo100544v
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Construction/Stereoselective Functionalization Cascade: Total Synthesis of Pachastrissamine (Jaspine B) through Palladium-Catalyzed Bis-cyclization of Propargyl Chlorides and Carbonates

Abstract: Palladium(0)-catalyzed cyclization of bromoallenes, propargyl chlorides, and carbonates bearing hydroxy and benzamide groups as internal nucleophiles stereoselectively provides functionalized tetrahydrofuran. Cyclization reactivity is dependent on the relative configuration of the benzamide and leaving groups, and on the nature of the leaving groups. This bis-cyclization was used as the key step in a short total synthesis of pachastrissamine, which is a biologically active marine natural product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Late-stage introduction of the side-chain makes it easy to synthesize derivatives bearing various side chains at the C-2 position. 7,16,27) To construct the cyclic structure of 5, we planned to employ cyclization of monotosylate 7. Compound 7 would be obtained from 1,2,4-triol 9 via selective tosylation of the primary alcohols catalyzed by dibutyltin oxide (Bu 2 SnO).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Late-stage introduction of the side-chain makes it easy to synthesize derivatives bearing various side chains at the C-2 position. 7,16,27) To construct the cyclic structure of 5, we planned to employ cyclization of monotosylate 7. Compound 7 would be obtained from 1,2,4-triol 9 via selective tosylation of the primary alcohols catalyzed by dibutyltin oxide (Bu 2 SnO).…”
Section: Resultsmentioning
confidence: 99%
“…9,10) Because of its novel structural features and impressive biological activity, many total syntheses of 1 have been accomplished. [3][4][5][6][7][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The stereoisomers of 1 have also been synthesized, 5,6,[20][21][22][23][24][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40] and their biological activity investigated. Interestingly, the 2-epimer 2 6,…”
mentioning
confidence: 99%
“…Jaspine B exhibits cytotoxic activity against various tumour cell lines at the nanomolar level and therefore prompts a wide interest in its synthesis 67. Various pachastrissamine derivatives were prepared and reported in separate work 68. Furthermore, propargylic chlorides could be used for the same transformation.…”
Section: Versatile Building Blocks In Pd‐catalyzed Cascadesmentioning
confidence: 99%
“…It was also reported that pachastrissamine and its stereoisomers inhibit sphingosine kinases (SphKs) and atypical protein kinase C [ 5 ]. Because of its intriguing biological activity, it has been an interesting target for synthetic chemists, and various synthetic routes to pachastrissamine have been reported [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. However, the structure-activity relationship (SAR) of pachastrissamine remains relatively unreported.…”
Section: Introductionmentioning
confidence: 99%